Pembiayaan Murabahah Bank Mandiri Syariah dan Pengaruhnya Terhadap Profitabilitas Unit Usaha Mikro Kecil dan Menengah Tahun 2016: Studi Kasus di Bank Mandiri Syariah Kantor Cabang Ponorogo - Andriyansyah, Diky (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
The aims of this research are to find out the murabaha products provided for the customers of the Mandiri Bank of Syariah Ponorogo branch office, especially the customers who focus on small and medium enterprises. To know the level of profitability of small and medium enterprises from murabaha financing of Mandiri Bank of Syariah Ponorogo branch office in 2016. And know the effect of murabaha financing of Mandiri Bank of Syariah Ponorogo branch office to the profitability of small and medium enterprises in Ponorogo regency. This research is quantitative research by using questionnaire method to collecting data. The results of this study are: Murabaha financing of Mandiri Bank of Syariah Ponorogo branch office are grouped in three categories: 34, 28% is high category, 51,42% is middle category, and 14, 28% is low category. Profitability of small and medium enterprises in Ponorogo regency in 2016 are grouped in three categories: 45,71% is high category, 42,85% is middle category, and 11,42% is low category. There is a significant effect of murabaha financing on profitability of small and medium enterprises in Ponorogo regency in 2016, because ro (0,447) > rt on db = 35 on level of significance 5% as well as rt on level of significance 1%, so Ha is received an Ho is refused. Keywords: Pembiayaan murabahah, Bank Mandiri Syariah, profitabilitas, unit usaha mikro kecil dan menengah.